STUDY OF EGALITARIANISM IN THE SOCIAL LIFE OF THE OSING COMMUNITY IN BANYUWANGI: ASPECTS OF WELFARE, JUSTICE AND EQUALITY: Kajian Egalitarianisme Dalam Kehidupan Sosial Masyarakat Osing Di Banyuwangi: Aspek-Aspek Kesejahteraan, Keadilan, Dan Kesetaraan - Adita Taufik Widianto; Mahfud (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
This research discusses the study of egalitarianism in the social life of the Osing community in Banyuwangi, by highlighting aspects of welfare, justice and equality. The Osing people have a strong belief in the principles of egalitarianism which prioritize social equality and justice in the treatment of individuals, regardless of background or social position. The method used in this research is the research method used is a qualitative research method. Research was conducted on the Osing community in Banyuwangi. The collection technique uses data triangulation where the collection uses primary data and secondary data. The results of this research can be concluded that the study of egalitarianism in the social life of the Osing community in Banyuwangi has important implications in understanding and promoting the values ​​of equality, justice and prosperity in the context of that society. This study provides a richer picture of how the values ​​of egalitarianism are reflected in the life patterns of local communities and helps in formulating strategies and policies that can increase equality and prosperity for all members of the Osing community.